The article presents the analysis results of the production processes aimed at service production. The main features of service production are described and the terms of service production are formulated. It has been demonstrated, that airports can be considered as a service production enterprise. The specific features of the production peculiar to airports are noted. The production process at the airport is associated with the need to fulfill certain processes in real time, the presenceof random factors affecting the process (weather conditions, schedule changes, etc.), special safety requirements, which lead to increase of the role of production informatization - I. M. Dalinger (Научный вестник МГТУ ГА)
The article presents the analysis results of the production processes aimed at service production. The main features of service production are described and the terms of service production are formulated. It has been demonstrated, that airports can be considered as a service production enterprise. The specific features of the production peculiar to airports are noted. The production process at the airport is associated with the need to fulfill certain processes in real time, the presenceof random factors affecting the process (weather conditions, schedule changes, etc.), special safety requirements, which lead to increase of the role of production informatization.